1992
DOI: 10.1073/pnas.89.17.8298
|View full text |Cite
|
Sign up to set email alerts
|

Increased tyrosine kinase activity of c-Src during calcium-induced keratinocyte differentiation.

Abstract: In cultured human epidermal keratinocytes, induction of differentiation by Ca2+ and ionophore treatment was found to result in rapid elevation of c-Src tyrosine kinase activity and inactivation of the c-Yes tyrosine kinase. Activation of c-Src kinase was accompanied by tyrosine dephosphorylation, which might be explained by a rapid increase in intracellular protein-tyrosine phosphatase activity. Ca2+-induced differentiation was also associated with altered tyrosine phosphorylation of several cellular proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 36 publications
9
77
2
Order By: Relevance
“…The mechanisms by which changes in extracellular Ca 2ϩ signal a change in the proliferation of keratinocytes have not yet been established. Exposing keratinocytes to elevated extracellular Ca 2ϩ is associated with an increase in the kinase activity of c-SRC and a decrease in the activity of c-YES (6,32); the mechanism producing this response has not been established. An increase in the apparent phosphorylation of an approximately 62-kDa protein co-immunoprecipitated with antirasGAP antibodies has also been demonstrated and attributed to activation of a calcium-binding receptor as opposed to Ca 2ϩ influx (7,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which changes in extracellular Ca 2ϩ signal a change in the proliferation of keratinocytes have not yet been established. Exposing keratinocytes to elevated extracellular Ca 2ϩ is associated with an increase in the kinase activity of c-SRC and a decrease in the activity of c-YES (6,32); the mechanism producing this response has not been established. An increase in the apparent phosphorylation of an approximately 62-kDa protein co-immunoprecipitated with antirasGAP antibodies has also been demonstrated and attributed to activation of a calcium-binding receptor as opposed to Ca 2ϩ influx (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of extracellular calcium levels has been associated with increased c-SRC kinase activity in keratinocytes (6). If the CaR is responsible for modulating c-SRC activity in response to changes in extracellular calcium, then an increase in SRC kinase activity should be observed in the presence of Gd 3ϩ , which binds and activates the CaR without passing through calcium channels.…”
Section: Effect Of Car Activity On C-src Kinase Activitymentioning
confidence: 99%
“…Activation of Src kinase requires Ca 2+ and can occur as a result of increased [Ca 2+ ] i (22,23). In our previous study, we have shown lysoPC-induced TRPC6 externalization in BAECs was not blocked in Ca 2+ -free KR buffer or by using BAPTA/AM (25 μM) (3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both proteins colocalize in discrete structures in specific areas in the periphery of the cell, indicating that these focal adhesions may differ in terms of their protein content and partners that are mediated by the PDZ domains of MDA-9/syntenin. Of potential interest, both proteins also colocalize in or near the cell nucleus, suggesting that these two proteins could interact and may promote transcriptional activities (7,8,19).…”
Section: Mda-9/syntenin Physically Interacts With C-src Which Correlmentioning
confidence: 99%